Statin potency and the risk of hospitalization for community‐acquired pneumonia. (29th January 2017) - Shin, Ju‐Young; Eberg, Maria; Ernst, Pierre; Filion, Kristian B.
Abstract : Aim: Previous studies suggest that statins may have beneficial respiratory effects. However, it is unclear if these purported benefits vary with statin potency. Our objective was to determine if higher potency statins, compared with lower potency statins, were associated with a reduced risk of hospitalization for community‐acquired pneumonia (HCAP). Methods: We conducted a nested case–control analysis of a retrospective, population‐based cohort of new users of statins using data extracted from the UK's Clinical Practice Research Datalink and Hospital Episode Statistics. For each HCAP case, we used risk set sampling to randomly select up to 10 controls, matched on sex, age, cohort entry date and follow‐up duration. We used conditional logistic regression with high‐dimensional propensity scores to estimate hazard ratios (HRs) and 95% confidence intervals (CIs) for HCAP with current use of higher potency statin vs. lower potency statins. Results: A total of 217 721 patients entered the cohort on a lower potency statin and 130 707 entered on a higher potency statin; these patients resulted in 2251 cases of HCAP during 561 886 person‐years of observation (rate: 4.0 HCAP per 1000 persons per year, 95% CI: 3.8–4.2). The analysis included 22 178 matched controls. Compared with lower potency statins, higher potency statins were associated with an increased rate of HCAP (HR: 1.14, 95% CI: 1.03–1.27). Higher potency statins were also associated with an increased rate of fatal HCAP (HR: 1.29, 95% CI: 1.04–1.59). Conclusions: Higher potency statins were not associated with a decreased risk of HCAP compared with lower potency statins.